2018
DOI: 10.18632/oncotarget.24590
|View full text |Cite|
|
Sign up to set email alerts
|

BAG3 promotes tumour cell proliferation by regulating EGFR signal transduction pathways in triple negative breast cancer

Abstract: Triple-negative breast cancer (TNBC), is a heterogeneous disease characterised by absence of expression of the estrogen receptor (ER), progesterone receptor (PR) and lack of amplification of human epidermal growth factor receptor 2 (HER2). TNBC patients can exhibit poor prognosis and high recurrence stages despite early response to chemotherapy treatment. In this study, we identified a pro-survival signalling protein BCL2- associated athanogene 3 (BAG3) to be highly expressed in a subset of TNBC cell lines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…In the KIT -low group we marked BAG3, SH3BP5 , and MARCKS genes as their high expression is associated with a poor prognosis (Figure 5D). BAG3 (BCL2-associated athanogene 3) knockdown is known to affect proliferation, migration, and invasion of EGFR-positive triple-negative breast cancer cell lines via AKT and FAK kinases (47). MARCKS (Myristoylated alanine-rich C kinase substrate) is involved in the tumorigenesis of different types of malignant diseases, but its role in myeloid malignances has not been described.…”
Section: Resultsmentioning
confidence: 99%
“…In the KIT -low group we marked BAG3, SH3BP5 , and MARCKS genes as their high expression is associated with a poor prognosis (Figure 5D). BAG3 (BCL2-associated athanogene 3) knockdown is known to affect proliferation, migration, and invasion of EGFR-positive triple-negative breast cancer cell lines via AKT and FAK kinases (47). MARCKS (Myristoylated alanine-rich C kinase substrate) is involved in the tumorigenesis of different types of malignant diseases, but its role in myeloid malignances has not been described.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent advances have resulted in approval of PPIis for marketing [ 550 ]. Disrupting the BAG3-HSP70 interaction has been demonstrated to sensitize TNBC cells to EGFRis [ 419 ]. BCL2-associated athanogene 3 (BAG3) is a co-chaperone for heat shock protein 70 (HSP70) and heat shock cognate 71 kDa (HSC70) chaperone proteins [ 551 , 552 ].…”
Section: Combination Strategy For Overcoming Egfri Resistance In Tnbcmentioning
confidence: 99%
“…In line with these findings, Shields et al reported that BAG3 is highly expressed in a subset of TNBC cell lines and primary tumor samples, while high expression of BAG3 in TNBC patients was associated with reduced recurrence-free survival, supporting the impact of BAG3 as an adverse prognostic factor [34]. The authors also observed a positive correlation between BAG3 and EGFR expression in TNBC cells and a direct interaction between BAG3 and EGFR signaling network components using a mass spectrometry approach.…”
Section: Breast Cancermentioning
confidence: 72%
“…The authors also observed a positive correlation between BAG3 and EGFR expression in TNBC cells and a direct interaction between BAG3 and EGFR signaling network components using a mass spectrometry approach. In TNBC cells, the combined targeting of BAG3 and EGFR was superior to inhibition of EGFR with Cetuximab alone, again highlighting the potential of BAG3 as a therapeutic target in TNBC [34].…”
Section: Breast Cancermentioning
confidence: 94%